Natural History of Established and De Novo Inflammatory Bowel Disease After Liver Transplantation for Primary Sclerosing Cholangitis. Issue 5 (7th March 2018) - Mouchli, Mohamad A; Singh, Siddharth; Boardman, Lisa; Bruining, David H; Lightner, Amy L; Rosen, Charles B; Heimbach, Julie K; Hasan, Bashar; Poterucha, John J; Watt, Kymberly D; Kane, Sunanda V; Raffals, Laura E; et al.
Abstract: Background: The course of inflammatory bowel disease (IBD) after liver transplantation (LT) for primary sclerosing cholangitis (PSC) is poorly understood. We describe the natural history of established IBD after LT (including risk of disease progression, colectomy, and neoplasia) and de novo IBD. Methods: In a retrospective cohort, we identified all patients with PSC who underwent LT for advanced PSC at Mayo Clinic, Rochester, Minnesota. Risk factors were identified using multivariate Cox proportional hazard analysis. Results: Three hundred seventy-three patients were identified (mean age, 47.5 ± 11.7 years; 64.9% male). Over a median (range) of 10 (5.5–17.1) years, 151 patients with PSC-IBD with an intact colon at the time of LT were studied. Post-LT, despite transplant-related immunosuppression, 56/151 (37.1%) required escalation of therapy, whereas 87 had a stable course (57.6%) and 8 patients (5.3%) improved. The 1-, 5-, and 10-year risks of progression of IBD were 4.0%, 18.5%, and 25.5%, respectively. On multivariate analysis, tacrolimus-based immunosuppression post-LT were associated with unfavorable course, and azathioprine use after LT was associated with improved course post-LT. Of 84 patients with no evidence of IBD at the time of LT, 22 (26.2%) developed de novo IBD post-LT. The 1-, 5-, and 10-year cumulative incidences of de novo IBD were 5.5%, 20.0%, and 25.4%, respectively. On univariate analysis, mycophenolate mofetil use after LT was associated with increased risk of de novo IBD, but azathioprine use after LT seemed to be protective. Conclusions: The 10-year cumulative probability of IBD flare requiring escalation of therapy after LT for PSC was 25.5%, despite immunosuppression for LT. The 10-year cumulative risk of de novo IBD after LT for PSC was 25.4%. Transplant-related immunosuppression may modify the risk of de novo IBD, with an increased risk with mycophenolate and a decreased risk with azathioprine.